Psychological- social consequences chemical bombardment of the Sardasht victims (a qualitative study) - B. Malkari; N. Karimian (Afarand Scholarly Publishing Institute, 2013)
Purpose: Aim of the present research is study of psychic and social consequences of chemical bombarding on the victims of Sardasht City by qualitative method.  Material & Method: 15 men and 15 women of Sardasht City victims were selected as available sampling and they were interviewed in semi-structured manner. Method of qualitative research is interpretive. Results of the interviews were divided into several categories.  Results: Results show that psychic and social consequences of chemical bombarding on the victims include complaints such as social complaints, psychic complaints, exhaustion problems, economical complaints, characteristic complaints, anger, no safety sensation, emotional interdependent, decrease of social interaction exist in victims.  Conclusion: Results of the research demonstrate social and psychological problems have higher role in psychic- social consequences of chemical bombarding in ratio with other psychic- social consequences. Finally, we involved in limitations and providing several recommendations